Thank you for registering.

One of our academic counsellors will contact you within 1 working day.

Please check your email for login details.
MY CART (5)

Use Coupon: CART20 and get 20% off on all online Study Material

ITEM
DETAILS
MRP
DISCOUNT
FINAL PRICE
Total Price: Rs.

There are no items in this cart.
Continue Shopping

Show that. (a – b) (a + b) + (b – c) (b + c) + (c – a) (c + a) = 0

Show that.
(a – b) (a + b) + (b – c) (b + c) + (c – a) (c + a) = 0

Grade:12

1 Answers

Harshit Singh
askIITians Faculty 5875 Points
2 months ago
Dear Student

LHS = (a–b) (a + b) + (b–c) (b + c) + (c–a) (c + a)
=a^2- b^2+ b^2- c^2+ c^2- a^2
= 0
= RHS

Thanks

Think You Can Provide A Better Answer ?

Provide a better Answer & Earn Cool Goodies See our forum point policy

ASK QUESTION

Get your questions answered by the expert for free